Purchasing power of money and methods of its measurement ("Journal "U". Economy. Management. Finance.", 2026)
The article expolores the concept of the purchasing power of money and substantiates approaches to its measurement from both theoretical and applied perspectives.
Keywords: purchasing power of money; purchasing power of the monetary unit; price level; money in circulation; inflation; purchasing power measurement; consumer basket; subsistence minimum